The Role of the Social Sector in the Islamic Economic Model: Evidence from Indonesia - Muttaqin, Aminnullah Achmad; Noor, Iswan; Afifah, Nurul; Syahrin, Fira Alfi (El-Barka, 2023)
Indonesia is the most generous country. Since the time of the Islamic Kingdom, there are forms of social funds, like zakat, infaq, alms, waqf, qurban, and grants. The existence and activities of Social Organisations and Social Non-Profit Institutions (ORSOLANILA) collections and distributions of funds have so far not been taken into account in national income. Whereas their actions can help to improve the Indonesian economy. Therefore, this study aims to examine the importance of ORSOLANILA in Indonesia and support the Islamic macroeconomic theory proposed by Dumairy. The method used in this research is descriptive qualitative with the type of library research. The results of this study state that ORSOLANILA’s roles are crucial in the national economy. Comparison data between Social Fund and Real GDP shows that have the different trend. Social funds increased while Real GDP dropped in the same period. This can show that the number of social funds when included in the macroeconomic calculation as a social sector can increase the amount of GDP. So it is necessary to pay attention to the Islamic economic model in calculating national income because of its impact which is provide a mechanism for economic stabilization in situations crisis or disaster and increasing investment in social and infrastructure projects that support long-term economic growth.